(untitled) (World Bulletin of Public Health, 2024)
In the morbidity structure of frequently ill children (FIC), repeated upper respiratory tract infections (URI) predominate; 10–15% of FRIs have lower respiratory tract infections (LRTI), and, as a rule, this category of children is not susceptible to infections in other body systems: gastrointestinal tract, central nervous system, urogenital tract or skin.